Avaliação do comportamento eletroquímico, caracterização microestrutural e mecânica dos aços inoxidáveis fundidos ASTM A 890/A 890M grau 1B e 3A - Lima, Hillane Mirelle Lopes Ferreira de (2019)
In this work two duplex stainless steels ASTM A890 grade 1B and 3A were investigated. Different hardness levels were produced by solution annealing heat treatment followed by isothermal aging at 450, 500, 550 and 600° C for 1 hour. The interest in the early stages of aging is the possibility of performing heat treatments capable of hardening the material, with minimal detrimental effects on corrosion resistance. Grade 1B steel contains 3.01 wt.% Cu and grade 3A steel is Cu free. Although the effect of copper on the mechanical properties of stainless steels is known, there are many controversies in the literature concerning its performance against localized corrosion of cast alloys in chloride-containing media. In addition, there is limited information available on the corrosion resistance of these alloys in environments with a high concentration of chloride, sulphide (HS-, S-) and gases such as H 2 S, CO 2 and O 2 . The research on the limits of the use of these steels under critical conditions can be very important, as the oil industry is in full growth in Brazil and with it also grows the demand for materials increasingly resistant to harsh environments and conditions severe. The performance against the corrosion of the alloys was evaluated by means of electrochemical techniques in different media and aggressive conditions. The work has four sections according to the test medium or condition: the first section corresponds to the study of the media (i) 0.6 mol/L NaCl; (ii) 0.3 mol/L H 2 SO 4 ; and (iii) 0.6 mol/L NaCl + 0.3 mol/L H 2 SO 4 ; the second corresponds to the media (iv) 0.6 mol/L NaCl + sodium thiosulphate (10 -3 mol /L); (v) 0.6 mol/L NaCl + CO 2 (sat.); and (vi) 0.6 mol/L NaCl + CO 2 (sat.) + sodium thiosulfate (10 -3 mol/ L); section three addresses the Critical pitting temperature studies, and finally, section four addresses the analyzes under dynamic conditions with the use of the rotating disk electrode. The microstructural characterization was done by optical microscopy, scanning electron and transmission. The study of the mechanical properties was performed by hardness measurements. The results showed that the effect of copper on the alloy depends on the pH of the medium, applied potential, presence of chloride and temperature.